The Role of Communicative Classroom Activities in Foreign Language Acquisition: The Case of Short Stories - Barkat, Turqui (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2021)
The present work advocates the use of short stories as an efficient communicative teaching technique to develop foreign language proficiency. We hypothesize that short stories in a TEFL context would particularly enhance three major components of foreign language learning namely, reading comprehension, vocabulary expansion and cultural awareness. The sample study will be represented by the second year Master students of Applied Language Studies at Mohamed Khider University of Biskra, Algeria. In fact, a pilot investigation will be conducted through the organization of four workshops which will be devoted to the precise evaluation of this technique of English language teaching with respect to two pre-determined objectives. The first one is the increase of students’ motivation and enjoyment and, the second, its positive repercussion that would eventually acknowledge our preconisation that short stories – within a communicative approach framework-constitute an essential pedagogical tool in the foreign language learning process.
Keywords: تدريس اللغة الإنجليزية -- اللغة الإنجليزية كلغة أجنبية -- النصوص الأدبية -- القصص القصيرة